2008
DOI: 10.1002/hep.21992
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus precore protein augments genetic immunizations of the truncated hepatitis C virus core in BALB/c mice

Abstract: DNA immunization has been used to induce either humoral or cellular immune responses against many antigens, including hepatitis C virus (HCV). In addition, DNA immunizations can be enhanced or modulated at the nucleotide level. Genetic immunizations were examined in BALB/c mice through the use of plasmids and chimeric DNA constructs encoding HCV core proteins and hepatitis B virus (HBV) precore (preC) regions. Plasmids encoding the truncated HCV core induced potent humoral and cellular responses to HCV; pcDNA3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Truncating the HCV core protein could improve its immunogenicity and evoke stronger immune responses in DNA-vaccinated mice. These findings are largely consistent with those of previous studies (27). We demonstrated that DNA immunization using the truncated HCV core protein induced specific T-and B-cell responses in a dose-dependent manner, while no significant improvement of immune responses could be reached by administration of increased doses of plasmids expressing the full-length HCV core protein.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Truncating the HCV core protein could improve its immunogenicity and evoke stronger immune responses in DNA-vaccinated mice. These findings are largely consistent with those of previous studies (27). We demonstrated that DNA immunization using the truncated HCV core protein induced specific T-and B-cell responses in a dose-dependent manner, while no significant improvement of immune responses could be reached by administration of increased doses of plasmids expressing the full-length HCV core protein.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies indicated that DNA vaccination with plasmids encoding the fulllength HCV core protein led to low levels of B-and Th-cell responses (18,27). Enhancement of the expression of the HCV core gene does not enhance core-specific immune responses in DNA immunization (2).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations